If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x(2x + -13) = 15 Reorder the terms: 5x(-13 + 2x) = 15 (-13 * 5x + 2x * 5x) = 15 (-65x + 10x2) = 15 Solving -65x + 10x2 = 15 Solving for variable 'x'. Reorder the terms: -15 + -65x + 10x2 = 15 + -15 Combine like terms: 15 + -15 = 0 -15 + -65x + 10x2 = 0 Factor out the Greatest Common Factor (GCF), '5'. 5(-3 + -13x + 2x2) = 0 Ignore the factor 5.Subproblem 1
Set the factor '(-3 + -13x + 2x2)' equal to zero and attempt to solve: Simplifying -3 + -13x + 2x2 = 0 Solving -3 + -13x + 2x2 = 0 Begin completing the square. Divide all terms by 2 the coefficient of the squared term: Divide each side by '2'. -1.5 + -6.5x + x2 = 0 Move the constant term to the right: Add '1.5' to each side of the equation. -1.5 + -6.5x + 1.5 + x2 = 0 + 1.5 Reorder the terms: -1.5 + 1.5 + -6.5x + x2 = 0 + 1.5 Combine like terms: -1.5 + 1.5 = 0.0 0.0 + -6.5x + x2 = 0 + 1.5 -6.5x + x2 = 0 + 1.5 Combine like terms: 0 + 1.5 = 1.5 -6.5x + x2 = 1.5 The x term is -6.5x. Take half its coefficient (-3.25). Square it (10.5625) and add it to both sides. Add '10.5625' to each side of the equation. -6.5x + 10.5625 + x2 = 1.5 + 10.5625 Reorder the terms: 10.5625 + -6.5x + x2 = 1.5 + 10.5625 Combine like terms: 1.5 + 10.5625 = 12.0625 10.5625 + -6.5x + x2 = 12.0625 Factor a perfect square on the left side: (x + -3.25)(x + -3.25) = 12.0625 Calculate the square root of the right side: 3.473110997 Break this problem into two subproblems by setting (x + -3.25) equal to 3.473110997 and -3.473110997.Subproblem 1
x + -3.25 = 3.473110997 Simplifying x + -3.25 = 3.473110997 Reorder the terms: -3.25 + x = 3.473110997 Solving -3.25 + x = 3.473110997 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3.25' to each side of the equation. -3.25 + 3.25 + x = 3.473110997 + 3.25 Combine like terms: -3.25 + 3.25 = 0.00 0.00 + x = 3.473110997 + 3.25 x = 3.473110997 + 3.25 Combine like terms: 3.473110997 + 3.25 = 6.723110997 x = 6.723110997 Simplifying x = 6.723110997Subproblem 2
x + -3.25 = -3.473110997 Simplifying x + -3.25 = -3.473110997 Reorder the terms: -3.25 + x = -3.473110997 Solving -3.25 + x = -3.473110997 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3.25' to each side of the equation. -3.25 + 3.25 + x = -3.473110997 + 3.25 Combine like terms: -3.25 + 3.25 = 0.00 0.00 + x = -3.473110997 + 3.25 x = -3.473110997 + 3.25 Combine like terms: -3.473110997 + 3.25 = -0.223110997 x = -0.223110997 Simplifying x = -0.223110997Solution
The solution to the problem is based on the solutions from the subproblems. x = {6.723110997, -0.223110997}Solution
x = {6.723110997, -0.223110997}
| (2x-13)=15 | | 16cos^2(x)+8cos(x)-2=0 | | -2(a+4)=6(a-2) | | 4.5z-2.5z=2.4 | | sin*2x+tg*x=-2 | | =0875 | | =.0875 | | 3x+4x+15= | | 14-6v=22 | | 10=4i-26 | | 5b+12=2b+18 | | 5/6*18 | | x(x+1)(x+2)(x+3)=3024 | | 220x+13=3313 | | 3(4+8x)=36x | | [x^2]=1/x | | v=zqt | | n=3n+12 | | 2225=4756y | | (6x+5)(6x+5)(3x+2)(x+1)=35 | | 4x-6x-3x= | | 5cosx-6=0 | | [3x^2-2/x^2] | | (200-4x)/3x | | k=2-3k | | 3(x)=2(x+7) | | x^2+y^2+4x+6y+13=0 | | 2(m-2)=3(m+4) | | 5(5+3x)=7(7+2x) | | 3x-11=x-2/3 | | 2p+2= | | 2cos1/2x=0 |